Dynamics of the Pollen Sequestrome Defined by Subcellular Coupled Omics. Issue 1 (14th July 2018) - Hafidh, Said; Potě¡il, David; Müller, Karel; Fíla, Jan; Michailidis, Christos; Herrmannová, Anna; Feciková, Jana; Ischebeck, Till; Valá¡ek, Leo¡ Shivaya; Zdráhal, Zbyněk; Honys, David
Abstract : The pollen sequestrome is found to be a highly dynamic compartment for the storage of translationally repressed mRNAs, and nontranslating monosomes are proposed to be the primary mediators of mRNA sequestration in Nicotiana tabacum. Abstract: Reproduction success in angiosperm plants depends on robust pollen tube growth through the female pistil tissues to ensure successful fertilization. Accordingly, there is an apparent evolutionary trend to accumulate significant reserves during pollen maturation, including a population of stored mRNAs, that are utilized later for a massive translation of various proteins in growing pollen tubes. Here, we performed a thorough transcriptomic and proteomic analysis of stored and translated transcripts in three subcellular compartments of tobacco ( Nicotiana tabacum ), long-term storage EDTA/puromycin-resistant particles, translating polysomes, and free ribonuclear particles, throughout tobacco pollen development and in in vitro-growing pollen tubes. We demonstrated that the composition of the aforementioned complexes is not rigid and that numerous transcripts were redistributed among these complexes during pollen development, which may represent an important mechanism of translational regulation. Therefore, we defined the pollen sequestrome as a distinct and highly dynamic compartment for the storage of stable, translationally repressed transcripts and demonstrated its dynamics. We propose that EDTA/puromycin-resistant particle complexes represent aggregated nontranslating monosomes as the primary mediators of messenger RNA sequestration. Such organization is extremely useful in fast tip-growing pollen tubes, where rapid and orchestrated protein synthesis must take place in specific regions.